Opera in the Viennese home from Mozart to Rossini - November, Nancy ca. 20./21. Jh (Cambridge University Press, 2024)
Domestic musical arrangements of opera provide a unique window on the world of nineteenth-century amateur music-making. These arrangements flourished in especially rich variety in early nineteenth-century Vienna. This study reveals ways in which the Viennese culture of musical arrangements opened up opportunities, especially for women, for connoisseurship, education, and sociability in the home, and extended the meanings and reach of public concert life. It takes a novel stance for musicology, prioritising musical arrangements over original compositions, and female amateurs' perspectives over those of composers, and asks: what cultural, musical, and social functions did opera arrangements serve in Vienna c.1790-1830? Multivalent musical analyses explore ways Viennese arrangers tailored large-scale operatic works to the demands and values of domestic consumers. Documentary analysis, using little-studied evidence of private and semi-private music-making, investigates the agency of musical amateurs and reinstates the central importance of women's roles